Students’ Assessment of Teaching of College - Rosmalin G. Arzagon; Melody A. Zaragoza; Sherry V. Mecida (Universitas Pendidikan Indonesia (UPI), 2023)
The primary objective of this descriptive study was to find out the students’ assessment of teaching among college teachers during the first semester of the academic year, 2021-2022. Based on the findings of the study, it is very consoling to note that the college faculty of Notre Dame of Tacurong College had remained steadfast in their commitment to carrying out the vision and mission of the institution to offer quality education to its clientele. This was evident that even in difficult times, their effort to adjust to the new normal mode of teaching and learning is noteworthy. The overall result is inspiring. However, the school can still do many things to improve or increase the knowledge of the college teachers on innovative methods of teaching to promote student learning. The approachability of teachers can be strengthened to help students in need of guidance to do their classwork correctly. Another recommendation is to conduct the same study in the middle of a term so that student feedback on teachers’ performance in delivering the lessons can be addressed immediately. In addition, it should be conducted with individual teachers and their specific subjects being taught.